Morphometric parameters of the proximal femoral epiphysis and their effect on the hip joint - Varda, Jovan; Valčić, Vanja; Blagojević, Valentina (Medicinski podmladak, 2022)
ABSTRACT Introduction: The femur is a long bone (ossa longa) that forms the hip and knee joints, supporting the weight of almost the entire body. This study is based on analyzing certain angles on the proximal femur that represent anthropometrically and surgically significant parameters, with clinical significance in diseases such as metabolic and degenerative bone disorders, arthritis, various hip trauma and disease. Aim: Determining the significance of certain morphometric parameters of the proximal femur and exploration of their impact on the hip joint. Materials and Methods: This cross-sectional study encompasses measuring four parameters, shaft length, the Collodiaphyseal angle (CDA), the Medial proximal femoral angle (MPFA) and the Lateral proximal femoral angle (LPFA), on femora belonging to the archive of the Institute of anatomy „Niko Miljanić“ of the Univerisity of Belgrade, Faculty of Medicine. A digital goniometer precise to two decimal places was used for all measurements. Results: Forty-seven femora were examined, 25 of which were left and 22 right femora of unknown gender and age, since none of the examined parameters could be used in procuring such information. The average femoral shaft length was 39.9±2.7 cm, the shortest 34.8 cm and the longest 45.7 cm. CDA was 127.64±4.25 degrees on average, with the minimum being 119.1 degrees and the maximum 137.7 degrees. Average LPFA was 87.21±3.07 degrees, the lowest 81.6 and the highest 93.0 degrees. MPFA was 86.9±3.73 degrees on average, with the smallest being 78.7 degrees and the largest 94.5 degrees. The MPFA of right femora was significantly lower than the MPFA of left femora (p=0,016). Conclusion: Eleven samples had a CDA below normal (<124°) with three being defined as coxa vara (CDA<120°). One had a CDA above normal (>135°), being defined as coxa valga. LPFA outside of reference values was determined on 11 samples, being below normal (<85°) in all of them, whilst MPFA had 13 with only one of them being below normal (<80°). Keywords: collodiaphyseal angle, Medial proximal femoral angle, Lateral proximal femoral angle, coxa vara, coxa valga